PICES Press, Vol. 22, No. 2, Summer 2014 - North Pacific Marine Science Organization (PICES) (North Pacific Marine Science Organization (PICES), 2014)
FUTURE and the FUTURE Open Science Meeting— The future of FUTURE (pp. 1-2); 2014 Inter-sessional Science Board Meeting: A note (pp. 3-5); More attractive science ecosystem design for FUTURE and beyond: A personal view (pp. 6-8); OSM Session on “Identifying multiple pressures and system responses in North Pacific marine ecosystems” (pp. 9-10); OSM Session on “Regional climate modeling in the North Pacific” (pp. 11-11); OSM Session on “Challenges in communicating science and engaging the public” (pp. 12-15); OSM Sessions on “Ecosystem status, trends, and forecasts” and “Ecosystem resilience and vulnerability” (pp. 16-17); OSM Session on “Strategies for ecosystem management in a changing climate” (pp. 18-19); OSM Workshop on “Top predators as indicators of climate change” (pp. 20-23); OSM Workshop on “Bridging the divide between models and decision-making” (pp. 24-26); OSM Workshop on “Climate change and ecosystem-based management of living marine resources” (pp. 27-28); OSM Workshop on an “Ecosystem projection model inter-comparison and assessment of climate change impacts on global fish and fisheries” (29-34); ICES Symposium on the “Ecological basis of risk analysis for marine ecosystems” (pp. 35-38); Human dimensions in the Russian Federation (pp. 39-42); Microbial Culture Collection at the National Institute for Environmental Studies, Tsukuba, Japan (pp. 43-45); The Bering Sea: Current status and recent trends (pp. 46-48); The state of the western North Pacific in the second half of 2013 (pp. 49-50); Unusual warming in the Gulf of Alaska (pp. 51-52); Obituary – Dr. Toshiro Saino (pp. 53-55); Program of topic sessions and workshops at PICES-2014 (pp. 56-56); 3rd International Symposium on “Effects of climate change on the world’s oceans” (pp. 57-57); PICES Interns (pp. 58-58)